2020
DOI: 10.1016/j.clinbiomech.2019.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of locations susceptible to osteoarthritis in patients with anterior cruciate ligament reconstruction: Combining knee joint computational modelling with follow-up T1ρ and T2 imaging

Abstract: Background: Finite element modelling can be used to evaluate altered loading conditions and failure locations in knee joint tissues. One limitation of this modelling approach has been experimental comparison. The aims of this proof-of-concept study were: 1) identify areas susceptible to osteoarthritis progression in anterior cruciate ligament reconstructed patients using finite element modelling; 2) compare the identified areas against changes in T 2 and T 1ρ values between 1-year and 3-year follow-up timepoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 80 publications
2
30
0
Order By: Relevance
“…3 Thus, early detection of articular cartilage damage can constitute an advantage in the prevention and treatment of the respective joint disease. 4 In addition to direct visualization of articular cartilage, quantitative magnetic resonance imaging (qMRI) provides numerical outcome measures that can be used to nondestructively evaluate early PTOA changes in the tissue. 5,6 MRI relaxation time mapping sequences such as T 1 , T 2 , continuous-wave T 1ρ (CWT 1ρ ), adiabatic T 1ρ (AdT 1ρ ), adiabatic T 2ρ (AdT 2ρ ), and relaxation along a fictitious field (T RAFF ) have been proposed as quantitative biomarkers for the assessment of articular cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…3 Thus, early detection of articular cartilage damage can constitute an advantage in the prevention and treatment of the respective joint disease. 4 In addition to direct visualization of articular cartilage, quantitative magnetic resonance imaging (qMRI) provides numerical outcome measures that can be used to nondestructively evaluate early PTOA changes in the tissue. 5,6 MRI relaxation time mapping sequences such as T 1 , T 2 , continuous-wave T 1ρ (CWT 1ρ ), adiabatic T 1ρ (AdT 1ρ ), adiabatic T 2ρ (AdT 2ρ ), and relaxation along a fictitious field (T RAFF ) have been proposed as quantitative biomarkers for the assessment of articular cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…The EMG-assisted MS model enables the inclusion of subject-specific muscle activation patterns that may alter in subjects with MS disorders [2427, 76, 77]. In addition, the FE model utilized a highly-detailed FRPVE soft tissue material model that has shown potentials if tissue-level mechanical responses, such as collagen fibril and nonfibrillar matrix strain, related to mechanically-induced cartilage adaptation and regeneration, are of interest [6, 3741, 43, 4648]. To assess and validate the developed pipeline, we investigated the knee joint loading and tissue mechanical responses during different daily activities of the individuals with KOA.…”
Section: Discussionmentioning
confidence: 99%
“…Summarizing, FE models utilizing subjectspecific joint geometries and complex FRPVE material models have shown great potential for estimating highly-detailed tissue mechanics and predicting cartilage damage and degeneration [6,39,43,[46][47][48]. However, creating the above-mentioned FRPVE FE models is a cumbersome manual task requiring several weeks of high-level expertise [48]. This process entails image segmentation, meshing, material model incorporation, estimation and application of loading and boundary conditions, and getting a converged solution.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, by using a biphasic transversely isotropic description, different authors were able to reproduce experimental cartilage stress-relaxation tests [92][93][94]. Bolcos et al [95] used a biphasic transversely isotropic model [60] to identify zones of knee cartilage susceptible to post-traumatic osteoarthritis. This demonstrated that constitutive models with this complexity level could simulate realistic responses of the tissue.…”
Section: Materials Constitutive Modelsmentioning
confidence: 99%